2018
DOI: 10.1007/s12094-018-1843-2
|View full text |Cite
|
Sign up to set email alerts
|

Stromal expression of JNK1 and VDR is associated with the prognosis of esophageal squamous cell carcinoma

Abstract: JNK1 and VDR act as tumor suppressors, and their stromal expression levels are associated with prognosis in esophageal squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…Vitamin D enters cells by two pathways: the steroid receptor pathway and the direct entry pathway. Vitamin D receptor (VDR) is a membrane receptor for vitamin D. However, whether VDR is a tumour suppressor or an oncogene remains unclear [27][28][29] . The VDR expressions in cisplatin and vitamin D treatments failed to show significant changes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D enters cells by two pathways: the steroid receptor pathway and the direct entry pathway. Vitamin D receptor (VDR) is a membrane receptor for vitamin D. However, whether VDR is a tumour suppressor or an oncogene remains unclear [27][28][29] . The VDR expressions in cisplatin and vitamin D treatments failed to show significant changes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…He et al showed that activating MAPK8 could induce autophagy and reduce apoptosis of cancer cells [34]. Bao et al found low expression of MAPK8 in ESCA, and showed that overexpression of MAPK8 could inhibit the proliferation and migration of cancer cells and was related to poor prognosis in ESCA patients [35]. CAPN10 is highly expressed in ESCA.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from endometrial cancer and nonneoplastic endometrial tissues using TRIzol RNA extraction agent (Invitrogen) according to the manufacturer's instructions 12. Only RNA that resulted in an A260/280 ratio of 1.8-2.0 was reverse transcribed to generate cDNA.…”
Section: Methodsmentioning
confidence: 99%